Flavonoid-Rich Ethanol Extract from the Leaves of Diospyros kaki Attenuates D-Galactose-Induced Oxidative Stress and Neuroinflammation-Mediated Brain Aging in Mice - Ma, Yingjuan (Oxid Med Cell Longev, 2018)
Aging is a major factor that contributes to neurological impairment and neuropathological changes, such as inflammation, oxidative stress, neuronal apoptosis, and synaptic dysfunction. Flavonoids act as protective antioxidant and anti-inflammatory agents against various age-related neurodegenerative diseases. Here, we investigated the protective effect and mechanisms of the flavonoid-rich ethanol extract from the leaves of Diospyros kaki (FELDK) in the cortex and hippocampus of D-galactose- (gal-) aged mice. Our results showed that FELDK treatment restored memory impairment in mice as determined by the Y-maze and Morris water maze tests. FELDK decreased oxidative stress levels via inhibiting reactive oxygen species (ROS) and malondialdehyde (MDA) production and elevating antioxidative enzymes. FELDK also alleviated D-gal-induced neuroinflammation via suppressing the expression of advanced glycation end products (AGEs) and receptor for AGEs (RAGE) and activating microgliosis and astrocytosis, nuclear factor kappa B (NF-κB) nuclear translocation, and downstream inflammatory mediators. Moreover, FELDK inhibited the phosphatidylinositol 3-kinase (PI3K)/Akt and C-jun N-terminal kinase (JNK) apoptotic signaling pathways and ameliorated the impairment of synapse-related proteins. Hence, these results indicate that FELDK exerts neuroprotective effects on D-gal-induced brain aging. Thus, FELDK may be a potential therapeutic strategy for preventing and treating age-related neurodegenerative diseases such as Alzheimer's disease.